Effect of individual tree volume on operational performance of harvester processor Efeito do volume individual de árvores no desempenho operacional do processador harvester - Rodrigues C.K. (2019)
© 2019, Fundacao de Pesquisas Florestais do Parana.The need to obtain multi-products from the forest makes the wood processing an important step in the timber harvest, being necessary, then, to understand the influence of the stand characteristics on the operational performance of the machines. The aim of this study was to evaluate the effect of the individual tree volume on the operational performance of the harvester forest processor in Pinus taeda L. stands, in order to assist in planning operations and reducing production costs. The analyzes were carried out by means of a time and motion study, determining the time consumed in the phases of the operational cycle, mechanical availability, operational efficiency, productivity, and production costs in three stands with different individual mean volumes (IMV): I (1.21 m3 tree-1); II (1.34 m3 tree-1) and III (1.61 m3 tree-1). In a completely randomized design, the averages of the variables were compared, as well as models for estimating productivity and production costs were fitted according to individual tree volume. The results showed that the processing element consumed a significant part of the total operational cycle time, with 46, 53 and 64% in treatments I, II and III, respectively, with an average operational efficiency of 56% in all treatments. Productivity increase and reduction of production costs were observed in the order of 43 and 30%, respectively, with the increase in IMV from 1.21 to 1.61 m3 tree-1. Such behavior can be represented by the third degree polynomial, which demonstrated the operational limit of 1.5 m3 tree-1 for the harvester forest processor.© 2019, Fundacao de Pesquisas Florestais do Parana.A necessidade da obtenção de multiprodutos da floresta faz com que o processamento da madeira seja uma etapa importante da colheita da madeira, sendo necessário entender a influência das características do povoamento no rendimento operacional das máquinas. Objetivou-se avaliar o efeito do volume individual das árvores no rendimento operacional do processador florestal harvester em povoamentos de Pinus taeda L., de modo a auxiliar o planejamento das operações e a redução dos custos de produção. As análises foram realizadas por meio de um estudo de tempos e movimentos, determinando os tempos consumidos nas fases do ciclo operacional, a disponibilidade mecânica, a eficiência operacional, a produtividade e os custos de produção em três povoamentos com diferentes volumes médios individuais (VMI): I (1,21 m3 árv-1); II (1,34 m3 árv-1) e III (1,61 m3 árv-1). Em um delineamento inteiramente casualisado, comparou-se as médias das variáveis, bem como ajustou-se modelos para estimativa da produtividade e dos custos de produção em função do volume individual das árvores. Os resultados mostraram que o elemento processamento consumiu parte significativa do tempo total do ciclo operacional com 46, 53 e 64% nos tratamentos I, II e III, respectivamente, com eficiência operacional média de 56% em todos os tratamentos. Foi observado um aumento de produtividade e redução de custos de produção na ordem de 43 e 30%, respectivamente, com o aumento do VMI de 1,21 para 1,61 m3 árv-1. Tal comportamento pode ser representado por meio do polinômio do terceiro grau, que demonstrou o limite operacional de 1,5 m3 árv-1 para o processador florestal harvester.